The Study of Chinese law in the United States: Reflections on the Past and Concerns about the Future - Stanley Lubman (Washington University Global Studies Law Review, 2003)
I first survey the development and current state of the field by reviewing American scholarship on some major areas of Chinese law from those early days up to the present. Then, against this background, I comment on the current scene and address the challenges that Chinese law continues to present to Western attempts at understanding China.
Keywords: Administration of justice; International law; Legal education; China; United States